Social development – a multidimensional approach to social development analysis. Country level evidence - Ewa Lechman (Gdańsk University of Technology, Faculty of Management and Economics, 2013)
The study investigates disparities in social development in 144 countries worldwide. In the paper we aim to investigate cross-country differences in social development level in year 2011, as well as to estimate inequalities on the field. Secondly, we assess relative social development level differences – gaps (divides) among countries. For the analysis purposes, we apply: descriptive statistics analysis, Kernel Epanechnikov density (to check for world distribution of social welfare), inequality measure – Gini coefficient and square Euclidean distance (full linkages) method. The analysis sample encompasses 144 countries, and we mainly collect statistical data for the year 2011 (if available). The data applied in the study are derived from databases like: United Nations Millennium Development Goals Database; United Nations Department of Economic and Social Affairs, Population Division; United Nations Educational, Scientific and Cultural Organization; World Health Organization; International Human Development Indicators
Keywords: I0; I2; I3; O15; O50; 330; social development; living standards; inequalities; Kernel distribution